Belief, Rice Culture, Climate Changed In Thailand (Journal of Namibian Studies : History Politics Culture, 2023)
An agriculture is major occupation of Thais. Farmers have local belief involved in the supernatural power of which can give them water or raining for their good crops. They built supernatural symbols for the respectful representing. These symbols are concerned animals differently. This article will explain the animal symbols related into entreat from supernatural power of which Thais believe that can help them gaining the good and enough crops or giving a luck for fishing. The data sources were collected from mass media, academic article, books linking to rainmaking ceremony in 3 regions: the northern, the northeastern, and the central region of Thailand while in the southern data are the animal symbols concerning the fishing. The finding was found the main 3 animals; snakehead fish, cat, frog in 3 regions while 3 main animal symbols in the southern are crab, fish, and shrimp. These believe symbolic animals have been presented in central of city or tourist area for showing and people’s respect. Before raining season each year, the people will arrange the rainmaking ceremony for good and enough crops. These believe concern to climate change situation in season change or overwhelmed on flood or drought that affect to food sustainability of Thai’s society.